General Considerations of Design and Development of Dosage Forms: Pre-formulation Review - Honmane, Sandip Mohan (Asian Journal of Pharmaceutics (AJP), 2017)
Goal of formulation development is to convert active drug moiety into suitable dosage forms. This can be achieved by investigating of physicochemical properties of a drug substance alone and along with excipients before the formulation. The main objective of pre-formulation testing is to collect the information useful to develop stable, bioavailable dosage forms with safety consideration. Pre-formulation investigations are designed to collect all necessary data, especially physicochemical, physico-mechanical, and biopharmaceutical properties of drug substances, excipients, and packaging materials. This review provides information about pre-formulation parameters such as physical, chemical, solubility, stability, storage, and precaution to be taken for ensure the quality of product.